Atypical presentation of the World Health Organization Grade 1 meningioma: A case report - Rajnish Kumar Jaiswal; Dasgupta, Sibaji (Asian Journal of Medical Sciences, 2022)
Meningiomas are the most common benign neoplasm of the brain whereas ectopic presentation, although reported, is rare. Among these ectopic tumors, there are a group of purely intraosseous meningiomas, which usually are diagnosed differentially from common primary osseous tumor such as fibrous dysplasia and osteoid osteoma. The World Health Organization (WHO) Grade 1 meningioma with an involvement of scalp, calvarial bone, dura, and brain seen rarely. This type of atypical presentation of the WHO Grade 1 meningioma rarely documented. The main theories to justify the unusual topography appear to be embryological remains of neuroectodermal tissue or cellular dedifferentiation. Surgical treatment seems the best curative option. Meningioma with bony involvement could be very aggressive tumor, need to prepare accordingly for surgery.